Speckle imaging at large telescopes: current results and future prospects - Horch, Elliott P (SPIE, 2016)
In recent years, speckle imaging has proven very useful for certain problems in single-Aperture high-resolution imaging, including searching for faint stellar companions near exoplanet host stars and for satellite imaging. These developments have largely been the result of the availability of electron-multiplying CCD cameras, which allow for greater sensitivity and better photometric linearity when compared with other detectors that have comparable speed. This in turn has led to an increased use for speckle imaging at mid-sized and large telescopes. Some results of these efforts will be discussed, and the outlook for the future of speckle will be given. © 2016 SPIE.
Keywords: CCD cameras; Electron multiplying ccds; Faint Companion Detection; Future prospects; High resolution; High-Resolution Astronomy; High-resolution imaging; Image Reconstruction; Image reconstruction; Interferometry; Large telescopes; Satellite imaging; Single aperture; Speckle; Speckle Imaging; Speckle imaging; Telescopes; dept.phy

Speckle interferometry of secondary components in nearby visual binaries - Tokovinin, Andrei; Horch, Elliott P (The Astronomical Journal, 2016)
Statistical characterization of secondary subsystems in binaries helps to distinguish between various scenarios of multiple-star formation. The Differential Speckle Survey Instrument was used at the Gemini-N telescope for several hours in 2015 July to probe the binarity of 25 secondary components in nearby solar-type binaries. Six new subsystems were resolved, with meaningful detection limits for the remaining targets. The large incidence of secondary subsystems agrees with other similar studies. The newly resolved subsystem HIP 115417 Ba,Bb causes deviations in the observed motion of the outer binary from which an astrometric orbit of Ba,Bb with a period of 117 years is deduced. © 2016. The American Astronomical Society. All rights reserved.
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: low-mass

Twinkle Twinkle Little Star - Speckle Imaging for Exoplanet Characterization - Howell, Steve B.; Scott, Nic; Horch, Elliott (American Astronomical Society, AAS Meeting, 2016)
The NASA K2 mission is finding many high-value exoplanets and world-wide follow-up is ensuing. The NASA TESS mission will soon be launched, requiring additional ground-based observations as well. As a part of the NASA-NSFNN-EXPLORE program to enable exoplanet research, our group is building two new speckle interferometry cameras for the Kitt Peak WIYN 3.5-m telescope and the Gemini-N 8-m telescope. Modeled after the successful DSSI visitor instrument that has been used at these telescopes for many years, speckle observations provide the highest resolution images available today from any ground- or space-based single telescope. They are the premier method through which small, rocky exoplanets can be validated. Available for public use in early 2017, WIYNSPKL and GEMSPKL will obtain simultaneous images in two filters with fast EMCCD readout, "speckle" and “wide-field” imaging modes, and user support for proposal writing, observing, and data reduction. We describe the new cameras, their design, and their benefits for exoplanet follow-up, characterization, and validation. Funding for this project comes from the NASA Exoplanet Exploration Program and NASA HQ.

Differential speckle and wide-field imaging for the Gemini-North and WIYN telescopes - Scott, Nicholas J; Howell, Steve B; Horch, Elliott P (SPIE, 2016)
Two new instruments are currently being built for the Gemini-North and WIYN telescopes. They are based on the existing DSSI (Differential Speckle Survey Instrument), but the new dual-channel instruments will have both speckle and "wide-field" imaging capabilities. Nearly identical copies of the instrument will be installed as a public access permanent loan at the Gemini-N and WIYN telescopes. Many exoplanet targets will come from the NASA K2 and TESS missions. The faint limiting magnitude, for speckle observations, will remain around 16 to 17th magnitude depending on observing conditions, while wide-field, high speed imaging should be able to go to 21+. For Gemini, the instrument will be remotely operable from either the mid-level facility at Hale Pohaku or the remote operations base in Hilo. © 2016 SPIE.
Keywords: High resolution imaging; High speed imaging; High-resolution imaging; Image reconstruction; Imaging capabilities; Instrumentation; Interferometry; NASA; Remote operation; Speckle; Speckle interferometry; Survey instruments; Telescopes; Wide field imaging; dept.phy

Speckle interferometry at SOAR in 2015 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2016)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope in 2015 are provided, totaling 1303 measurements of 924 resolved binary and multiple stars, and non-resolutions of 260 targets. The separations range from 12 mas to 3.″37 (median 0.″17); the maximum measured magnitude difference is 6.7 mag. We resolved 27 pairs for the first time, including 10 as inner or outer subsystems in previously known binaries, e.g., the 50 mas pair in Cha. Newly resolved pairs are commented upon. We discuss three apparently non-hierarchical systems that have been discovered in this series, arguing that their unusual configurations are the result of projection. The resolved quadruple system HIP 71510 is also studied. © 2016. The American Astronomical Society. All rights reserved..
Keywords: binaries: general; dept.phy; peer-reviewed

Speckle imaging excludes low-mass companions orbiting the exoplanet host star trappist-1 - Howell, Steve B; Everett, Mark E; Horch, Elliott P; Winters, Jennifer G; Hirsch, Lea A; Nusdeo, Dan; Scott, Nicholas J (The Astrophysical Journal, 2016)
We have obtained the highest-resolution images available of TRAPPIST-1 using the Gemini-South telescope and our speckle imaging camera. Observing at 692 and 883 nm, we reached the diffraction limit of the telescope providing a best resolution of 27 mas or, at the distance of TRAPPIST-1, a spatial resolution of 0.32 au. Our imaging of the star extends from 0.32 to 14.5 au. We show that to a high confidence level, we can exclude all possible stellar and brown dwarf companions, indicating that TRAPPIST-1 is a single star. © 2016. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; stars: imaging; stars: individual (TRAPPIST-1, 2MASS J23062928-0502285)

SCSI: the southern connecticut stellar interferometer - Horch, Elliott P; Weiss, Samuel A; Rupert, Justin D; Dimaio, Alex J; Nusdeo, Daniel A; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo; Giudice, Andrea (SPIE, 2016)
The construction of a new prototype visible-light intensity interferometer for use in stellar astronomy is described. The instrument is located in New Haven, Connecticut, at Southern Connecticut State University, but key components of the system are also portable and have been taken to existing research-class telescopes to maximize sensitivity and baseline. The interferometer is currently a two-station instrument, but it is easily expandable to several stations for simultaneous measurement using multiple baselines. The design features single photon avalanche diode (SPAD) arrays, which increase the throughput and signal-To-noise ratio of the instrument. Predicted system performance and preliminary observations will be discussed. © 2016 SPIE.
Keywords: Avalanche diodes; Design features; Intensity Interferometry; Interferometers; Interferometry; Particle beams; Photon Counting; Photon counting; Photons; Signal to noise ratio; Simultaneous measurement; Single Photon Avalanche Diode Arrays; Single photon avalanche diode; Single-photon avalanche diode arrays; Stars; Stellar interferometers; Timing Correlation; Ultra-High-Resolution Astronomy; Ultrahigh resolution; Visible light; dept.phy

Stellar companions to the exoplanet host stars HD 2638 and HD 164509 - Wittrock, Justin M; Kane, Stephen R; Horch, Elliott P; Hirsch, Lea A; Howell, Steve B; Ciardi, David R; Everett, Mark E; Teske, Johanna K (The Astronomical Journal, 2016)
An important aspect of searching for exoplanets is understanding the binarity of the host stars. It is particularly important, because nearly half of the solar-like stars within our own Milky Way are part of binary or multiple systems. Moreover, the presence of two or more stars within a system can place further constraints on planetary formation, evolution, and orbital dynamics. As part of our survey of almost a hundred host stars, we obtained images at 692 and 880 nm bands using the Differential Speckle Survey Instrument (DSSI) at the Gemini-North Observatory. From our survey, we detect stellar companions to HD-2638 and HD-164509. The stellar companion to HD-2638 has been previously detected, but the companion to HD-164509 is a newly discovered companion. The angular separation for HD-2638 is 0.512±0 002 and for HD-164509 is 0.697 0. 00 ' 2. This corresponds to a projected separation of 25.6±1.9 au and 36.5±1.9 au, respectively. By employing stellar isochrone models, we estimate the mass of the stellar companions of HD-2638 and HD-164509 to be 0.483±0.007-Me and 0.416 0.007 M, respectively, and their effective temperatures to be 3570±8K and 3450±7K, respectively. These results are consistent with the detected companions being late-type M dwarfs. © 2016. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HD 2638, HD 164509); techniques: high angular resolution

A quintuple star system containing two eclipsing binaries - Rappaport, S; Lehmann, H; Kalomeni, B; Borkovits, T; Latham, D W; Bieryla, Allyson; Ngo, Henry; Mawet, Dimitri; Howell, Steve B; Horch, Elliott P; Jacobs, T L; Lacourse, D; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We present a quintuple star system that contains two eclipsing binaries. The unusual architecture includes two stellar images separated by 11 arcsec on the sky: EPIC 212651213 and EPIC 212651234. The more easterly image (212651213) actually hosts both eclipsing binaries which are resolved within that image at 0.09 arcsec, while the westerly image (212651234) appears to be single in adaptive optics (AO), speckle imaging, and radial velocity (RV) studies. The 'A' binary is circular with a 5.1-d period, while the 'B' binary is eccentric with a 13.1-d period. The γ velocities of the A and B binaries are different by ~10 km s-1. That, coupled with their resolved projected separation of 0.09 arcsec, indicates that the orbital period and separation of the 'C' binary (consisting of A orbiting B) are ≃65 yr and ≃25 au, respectively, under the simplifying assumption of a circular orbit. Motion within the C orbit should be discernible via future RV, AO, and speckle imaging studies within a couple of years. The C system (i.e. 212651213) has an RV and proper motion that differ from that of 212651234 by only ~1.4 kms-1 and ~3 mas yr-1. This set of similar space velocities in three dimensions strongly implies that these two objects are also physically bound, making this at least a quintuple star system. © 2016 The Authors.
Keywords: Binaries: close; Binaries: eclipsing; Binaries: general; Binaries: spectroscopic; Binaries: visual; dept.phy; peer-reviewed

Two new long-period giant planets from the McDonald observatory planet search and two stars with long-period radial velocity signals related to stellar activity cycles - Endl, Michael; Brugamyer, Erik; Cochran, William D.; MacQueen, Phillip J.; Robertson, Paul; Meschiari, Stefano; Ramirez, Ivan; Shetrone, Matthew D.; Gullikson, Kevin; Johnson, Marshall C.; Wittenmyer, Robert A.; Horner, Jonathan; et al. (The Astrophysical Journal, 2016)
We report the detection of two new long-period giant planets orbiting the stars HD 95872 and HD 162004 (φ1 Dra B) by the McDonald Observatory planet search. The planet HD 95872b has a minimum mass of 4.6 MJup and an orbital semimajor axis of 5.2 AU. The giant planet φ1 Dra Bb has a minimum mass of 1.5 MJup and an orbital semimajor axis of 4.4 AU. Both of these planets qualify as Jupiter analogs. These results are based on over one and a half decades of precise radial velocity (RV) measurements collected by our program using the McDonald Observatory Tull Coude spectrograph at the 2.7 m Harlan J. Smith Telescope. In the case of φ1 Dra B we also detect a long-term nonlinear trend in our data that indicates the presence of an additional giant planet, similar to the Jupiter-Saturn pair. The primary of the binary star system, φ1 Dra A, exhibits a very large amplitude RV variation due to another stellar companion. We detect this additional member using speckle imaging. We also report two cases - HD 10086 and HD 102870 (β Virginis) - of significant RV variation consistent with the presence of a planet, but that are probably caused by stellar activity, rather than reflexive Keplerian motion. These two cases stress the importance of monitoring the magnetic activity level of a target star, as long-term activity cycles can mimic the presence of a Jupiter-analog planet. © 2016. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: activity; techniques: radial velocities

Three temperate neptunes orbiting nearby stars - Fulton, Benjamin J; Howard, Andrew W; Weiss, Lauren M; Sinukoff, Evan; Petigura, Erik A; Isaacson, Howard; Hirsch, Lea A; Marcy, Geoffrey W; Henry, Gregory W; Grunblatt, Samuel K; Huber, Daniel; Huber, Daniel; et al. (The Astrophysical Journal, 2016)
We present the discovery of three modestly irradiated, roughly Neptune-mass planets orbiting three nearby Solartype stars. HD 42618 b has a minimum mass of 15.4±2.4 M⊕, a semimajor axis of 0.55 au, an equilibrium temperature of 337 K, and is the first planet discovered to orbit the solar analogue host star, HD 42618. We also discover new planets orbiting the known exoplanet host stars HD 164922 and HD 143761 (p CrB). The new planet orbiting HD 164922 has a minimum mass of 12.9±1.6 M⊕ and orbits interior to the previously known Jovian mass planet orbiting at 2.1 au. HD 164922 c has a semimajor axis of 0.34 au and an equilibrium temperature of 418 K. HD 143761 c orbits with a semimajor axis of 0.44 au, has a minimum mass of 25±2 M⊕, and is the warmest of the three new planets with an equilibrium temperature of 445 K. It orbits exterior to the previously known warm Jupiter in the system. A transit search using space-based CoRoT data and ground-based photometry from the Automated Photometric Telescopes (APTs) at Fairborn Observatory failed to detect any transits, but the precise, high-cadence APT photometry helped to disentangle planetary-reflex motion from stellar activity. These planets were discovered as part of an ongoing radial velocity survey of bright, nearby, chromospherically inactive stars using the Automated Planet Finder (APF) telescope at Lick Observatory. The high-cadence APF data combined with nearly two decades of radial velocity data from Keck Observatory and gives unprecedented sensitivity to both short-period low-mass, and long-period intermediate-mass planets. © 2016. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; planetary systems; stars: individual (HD 42618, HD 164922, HD 143761)

K2 discovers a busy bee: an unusual transiting neptune found in the beehive cluster - Obermeier, Christian; Henning, Thomas; Schlieder, Joshua E.; Crossfield, Ian J. M.; Petigura, Erik A.; Howard, Andrew W.; Sinukoff, Evan; Isaacson, Howard; Ciardi, David R.; David, Trevor J.; Hillenbrand, Lynne A.; Beichman, Charles A.; et al. (The Astronomical Journal, 2016)
Open clusters have been the focus of several exoplanet surveys, but only a few planets have so far been discovered. The Kepler spacecraft revealed an abundance of small planets around small cool stars, therefore, such cluster members are prime targets for exoplanet transit searches. Kepler's new mission, K2, is targeting several open clusters and star-forming regions around the ecliptic to search for transiting planets around their low-mass constituents. Here, we report the discovery of the first transiting planet in the intermediate-age (800 Myr) Beehive cluster (Praesepe). K2-95 is a faint (Kp = 15.5 mag) dwarf from K2's Campaign 5 with an effective temperature of 3471 ±124 K, approximately solar metallicity and a radius of 0.402± 0.050.R⊕ We detected a transiting planet with a radius of3.47+0.78 -0.53R⊕ and an orbital period of 10.134 days. We combined photometry, medium/high-resolution spectroscopy, adaptive optics/speckle imaging, and archival survey images to rule out any false-positive detection scenarios, validate the planet, and further characterize the system. The planet's radius is very unusual as M-dwarf field stars rarely have Neptune-sized transiting planets. The comparatively large radius of K2-95b is consistent with the other recently discovered cluster planets K2-25b (Hyades) and K2-33b (Upper Scorpius), indicating systematic differences in their evolutionary states or formation. These discoveries from K2 provide a snapshot of planet formation and evolution in cluster environments and thus make excellent laboratories to test differences between field-star and cluster planet populations. © 2016. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; eclipses; peer-reviewed; stars: individual (K2-95); stars: low-mass; techniques: photometric; techniques: spectroscopic

197 candidates and 104 validated planets in k2's first five fields - Crossfield, Ian J M; Ciardi, David R; Petigura, Erik A; Sinukoff, Evan; Schlieder, Joshua E; Schlieder, Joshua E; Howard, Andrew W; Beichman, Charles A; Isaacson, Howard; Dressing, Courtney D; Christiansen, Jessie L; Fulton, Benjamin J; et al. (Astrophysical Journal Supplement Series, 2016)
We present 197 planet candidates discovered using data from the first year of the NASA K2 mission (Campaigns 0-4), along with the results of an intensive program of photometric analyses, stellar spectroscopy, high-resolution imaging, and statistical validation. We distill these candidates into sets of 104 validated planets (57 in multi-planet systems), false positives, and 63 remaining candidates. Our validated systems span a range of properties, with median values of RP= 2.3 R⊕, P = 8.6 days, Teff = 5300 K, and Kp = 12.7mag. Stellar spectroscopy provides precise stellar and planetary parameters for most of these systems. We show that K2 has increased by 30% the number of small planets known to orbit moderately bright stars (1-4 R R⊕, Kp = 9-13 mag). Of particular interest are planets smaller than 2 R⊕, orbiting stars brighter than Kp = 11.5 mag, 5 receiving Earth-like irradiation levels, and several multi-planet systems - including 4 planets orbiting the M dwarf K2-72 near mean-motion resonances. By quantifying the likelihood that each candidate is a planet we demonstrate that our candidate sample has an overall false positive rate of 15%-30%, with rates substantially lower for small candidates (<2R⊕) and larger for candidates with radii >8 R⊕ and/or with P<3 days. Extrapolation of the current planetary yield suggests that K2 will discover between 500 and 1000 planets in its planned four-year mission, assuming sufficient follow-up resources are available. Efficient observing and analysis, together with an organized and coherent follow-up strategy, are essential for maximizing the efficacy of planet-validation efforts for K2, TESS, and future large-scale surveys. © 2016. The American Astronomical Society. All rights reserved.
Keywords: catalogs; dept.phy; planets and satellites: fundamental parameters; planets and satellites: general; techniques: high angular resolution; techniques: photometric; techniques: spectroscopic